Analisis Surah Al-Hujurat dan Pemaknaan Menuju Aktualitas Pengamalan - Al Haq, Mursyid (Jurnal Garasi Buku dan Obrolan Keilmuan, 2023)
Manners include the main part discussed in surah Al-Hujurat, how to get along with Allah, the Messenger and fellow human beings. Interaction with humans has its own difficulties, it also causes many problems. So that Allah guides people through His Messenger to organize a good and prosperous life. Through a good relationship with Allah and His Messenger we get instructions towards a happy life. Surah Al-Hujurat verses 6-8 discusses Tabayyun checking news to prove its validity, obedience to the apostle, love for faith and hatred for its opponents and obstacles, and gifts given to those who are on the straight path and achieve true love of faith. Meanwhile, Tabayyun is a solution that the Qur'an offers in an increasingly sophisticated era of information and technology.